Trust and Ease of Use as Determinants of QRIS Adoption Intention among Culinary MSMEs in Indramayu Regency - Tiara Fitri Rizkiyah (Golden Ratio of Mapping Idea and Literature Format, 2026)
payment systems, including among culinary MSMEs in Indramayu Regency. QRIS emerges as an integrated digital payment innovation offering efficiency and convenience. Students, as the digital generation, represent a potential segment for QRIS adoption. This study was conducted to understand respondents’ perceptions and analyze the influence of trust and ease of use on interest in using QRIS. The research employs descriptive and associative methods with a quantitative approach, involving 96 respondents through purposive sampling and questionnaires as instruments. Research data was analyzed using simple and multiple linear regression via SPSS version 25. The findings reveal that the influence of trust and ease of use on interest in using QRIS are categorized as very good. Both t-tests and F-tests show that trust and ease of use have a significant positive influence on interest in using QRIS, both partially and simultaneously. Indicating that the higher trust and ease of use, result in the greater the students' interest in using QRIS for transactions in culinary MSMEs.